'All chemical substances are harmful.' public appraisal of uncertain risks of food additives and contaminants. (February 2020) - Jansen, Tom; Claassen, Liesbeth; van Kamp, Irene; Timmermans, Daniëlle R.M.
Abstract: In toxicological health risk assessment, epistemic uncertainties (e.g. about a chemical's intrinsic properties or toxicity) often remain, preventing definitive statements about whether a chemical constitues a risk. In this study, we analyzed public appraisals of uncertain risks of food additives and contaminants. We identified three major characteristics of public appraisal. First, hazard appraisals differed consistently from risk appraisals: respondents were less disturbed by a possible health risk than by the mere presence of the chemical substance in food. Second, while a majority understood that exposure determines whether a chemical constitutes a risk, many respondents thought that all chemicals are equally harmful. This suggests a mismatch between beliefs about exposure and beliefs about toxicity. Finally, the higher people valued certainty about food safety and the less they considered uncertainty about a risk acceptable, the more severe they appraised the presence of the chemical substance in food. This suggests that a mismatch between the level of uncertainty that people expect about food safety and the actual level of scientific uncertainty, affects how people evaluate the presence of chemical substances in food. Following the findings, implications for risk communication are discussed. Highlights: People are less disturbed by the possible risk of a chemical substance in food, than by the mere presence of the chemical in food. A large majority of the public understands that exposure determines whether a chemical constitutes a health risk. A significant minority of the public thinks that all chemicals are equally harmful. A mismatch between expected and actual uncertainty about food safety may affect the evaluation of the presence of chemicals in food.